Analisis Hubungan antara Kesadaran Metakognitif dengan Hasil Belajar Matematika dan IPA Siswa SMA di Kota Mataram - Lia Fitria; Jamaluddin Jamaluddin; I Putu Artayasa (Universitas Pendidikan Mandalika (UNDIKMA), 2020)
The purpose of this study was to investigate the relationship between metacognitive awareness with mathematics and science learning outcomes of high school students in the city of Mataram. This research is correlational research. Metacognitive awareness is measured by the Metacognitive Awareness Inventory. Student learning outcomes seen from the average value of report cards. The data analysis of this study used descriptive analysis and inferential statistical analysis through the product moment correlation test. The results of data analysis showed that 18.89% of students had metacognitive awareness in the excellent category; 80.31% with good category; and 0.78% in the medium category. Metacognitive awareness in each metacognition sub-component that has the highest score is the debugging strategy (79.74%) and the lowest is the evaluation sub-component (72.03%). Based on data analysis of students' mathematics and science learning outcomes it is known that the learning outcomes in the excellent category amounted to 70.47%. Student learning outcomes in the good category 29.25% and in the moderate category 0.78%. Hypothesis test results were performed using SPSS 16 with product moment correlation techniques obtained correlation coefficient r = 0.193 and the coefficient of determination R2 = 3.7%. The results of this hypothesis test indicate that there is a positive and significant correlation between metacognitive awareness and mathematics learning and science outcomes in high school students in the city of Mataram. The contribution of metacognitive awareness to mathematics and science learning outcomes of high school students was 3.7%.